Proceedings of the Proceedings of the 1st Workshop Multimedia Education, Learning, Assessment and Its Implementation in Game An 2019
DOI: 10.4108/eai.26-1-2019.2283201
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Corporate Social Responsibility Towards Purchase Intention: The Mediating Effect of Brand Image and Corporate Reputation

Abstract: The body of knowledge on Corporate Social Responsibility has grown tremendously over the past few decades. However, there are still gaps in the literature regarding CSR and its role in enhancing corporate strategy. This article aims at filling some of those gaps on whether CSR do enhance Brand Image and Corporate Reputation and influence Purchase Intention. List of questionnaires were distributed across Jabodetabek area with total respondents of 440. This study only considered respondents with knowledge on CSR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Numerous researchers have found evidence of the impact of corporate social responsibility on the intention to purchase (Gigauri, 2012). Other research using the focus group discussion also found that corporate social responsibility in the company will in one way or another affect the intention of the client's purchase, bearing in mind that it should be noted that the customer will not request such information instead he will wait to be informed (Abdullah & Budiman, 2019). Others also expounded that the impact of CSR on the buying intentions of consumers is more complicated than he thought where can CSR affect firms directly affect or indirectly, to the purchase intentions, where direct effect is when reflect the activities of corporate social responsibility and consumer or beliefs depending on the degree of consumer confidence that corporate social responsibility and institutional capacity as well as consumer support for the behavior of the social responsibility of companies.…”
Section: The Relationship Between Csr and Purchase Intentionmentioning
confidence: 95%
See 2 more Smart Citations
“…Numerous researchers have found evidence of the impact of corporate social responsibility on the intention to purchase (Gigauri, 2012). Other research using the focus group discussion also found that corporate social responsibility in the company will in one way or another affect the intention of the client's purchase, bearing in mind that it should be noted that the customer will not request such information instead he will wait to be informed (Abdullah & Budiman, 2019). Others also expounded that the impact of CSR on the buying intentions of consumers is more complicated than he thought where can CSR affect firms directly affect or indirectly, to the purchase intentions, where direct effect is when reflect the activities of corporate social responsibility and consumer or beliefs depending on the degree of consumer confidence that corporate social responsibility and institutional capacity as well as consumer support for the behavior of the social responsibility of companies.…”
Section: The Relationship Between Csr and Purchase Intentionmentioning
confidence: 95%
“…Companies must fully commitment with ethical responsibility towards shareholders, and society, to undertake ethical and correct work for all stakeholders (Abdullah & Budiman, 2019). Where consumer responses are mainly affected by the consumer's awareness of ethical responsibility, belief in them and the ability of companies to apply this responsibility and develop a general framework for the consumer's ethical response as well as how to stimulate suggestions that provide consumer support towards the ethical behavior of the company and then turn this support into a positive buying behavior (Deng & Qian, 2011).…”
Section: Ethical Responsibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, in this study, the researcher will only focus on employees' perceptions of CSR itself. Complementing the existing research, Abdullah & Budiman (2019), suggests that an organization can greatly benefit from CSR measures that are implemented properly.…”
Section: Perceived Corporate Social Responsibility (Pcsr)mentioning
confidence: 99%